Observation of Central Toroidal Rotation Induced by ICRF on EAST - 潘夏云 王福地 张新军 吕波 陈俊 李颖颖 符佳 石跃江 余羿 叶民友 万宝年 (Plasma science & technology, 2016)
Core plasma rotation of both L-mode and H-mode discharges with ion cyclotron range of frequency（ICRF） minority heating（MH） scheme was measured with a tangential X-ray imaging crystal spectrometer on EAST（Experimental Advanced Superconducting Tokamak）.Cocurrent central impurity toroidal rotation change was observed in ICRF-heated L-and H-mode plasmas.Rotation increment as high as 30 km/s was generated at ~1.7 MW ICRF power.Scaling results showed similar trend as the Rice scaling but with significant scattering,especially in L-mode plasmas.We varied the plasma current,toroidal field and magnetic configuration individually to study their effect on L-mode plasma rotation,while keeping the other major plasma parameters and heating unchanged during the scanning.It was found that larger plasma current could induce plasma rotation more efficiently.A scan of the toroidal magnetic field indicated that the largest rotation was obtained for on-axis ICRF heating.A comparison between lower-single-null（LSN）and double-null（DN） configurations showed that LSN discharges rendered a larger rotation change for the same power input and plasma parameters.